2019
DOI: 10.1371/journal.pone.0216486
|View full text |Cite
|
Sign up to set email alerts
|

Community acceptability of Seasonal Malaria Chemoprevention of morbidity and mortality in young children: A qualitative study in the Upper West Region of Ghana

Abstract: Background Malaria remains a major public health problem, especially in sub-Sahara African countries. The Malaria Control Program of Ghana has implemented Seasonal Malaria Chemoprevention (SMC) intervention in the Upper West Region in 2015. This preventive drug has been recommended by WHO as very safe and effective in preventing malaria in children under five years. This study assessed community acceptability of the SMC intervention in the Lawra district of Northern Ghana. Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
(19 reference statements)
3
21
0
Order By: Relevance
“…The good e cacy and generally favorable safety pro le, as well as the growing experience with this intervention drove the positive perception. Similar ndings have been reported by other researchers, including a recent publication of a qualitative study among parents and CHWs in the upper West region of Ghana which demonstrated that the high acceptability of the SMC intervention was driven by the perception that SMC had helped reduce the prevalence of malaria [20]. The success of SMC at the enduser level could not have been achieved without the early endorsement of the intervention by national stakeholders.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The good e cacy and generally favorable safety pro le, as well as the growing experience with this intervention drove the positive perception. Similar ndings have been reported by other researchers, including a recent publication of a qualitative study among parents and CHWs in the upper West region of Ghana which demonstrated that the high acceptability of the SMC intervention was driven by the perception that SMC had helped reduce the prevalence of malaria [20]. The success of SMC at the enduser level could not have been achieved without the early endorsement of the intervention by national stakeholders.…”
Section: Discussionsupporting
confidence: 85%
“…The consequences of poor adherence to the SMC program can be dramatic as it raises the risk of resistance emergence to the drugs used and impairs the e cacy of the intervention [21]. Although numerous studies tried to estimate adherence to SMC, it must be emphasized that, to date, there is little objective, quantitative data that con rm adherence (such as plasma drug levels) from areas where SMC is implemented as a routine program [20][21][22][23]. In the absence of such a standardized systematic measure of adherence, we investigated the causes for reduced adherence in order to identify measures that could increase access to SMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of de nite strati cation within this age group suggests that all children under 5 years of age are at high risk. In fact, a seasonal malaria chemoprevention program has been piloted, and shown to signi cantly reduce malaria in under 5 children participating in the mass drug administration program in different areas of diverse malaria transmission intensity (14)(15)(16)(17). Some economic bene t has further been attributed to seasonal malaria chemoprevention of all under 5 children (16,18), with recommendation for this approach to be integrated into the health system in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…shown to signi cantly reduce malaria in under 5 children participating in the mass drug administration program in different areas of diverse malaria transmission intensity (14)(15)(16)(17). Some economic bene t has further been attributed to seasonal malaria chemoprevention of all under 5 children (16,18), with recommendation for this approach to be integrated into the health system in endemic areas.…”
Section: Discussionmentioning
confidence: 99%